Dengue severity and profiles of complement activation and immune mediators: A multicenter cohort study in Indonesia - Ika Saptarini; Sri Masyeni; Alida Roswita Harahap; Astuti Giantini; Pringgodigdo Nugroho; Agus Handito; Harimat Hendarwan; Adityo Susilo; Sotianingsih Haryanto; Desi Fitriani; R. Tedjo Sasmono; Erni Juwita Nelwan (PLoS ONE, 2026)
Background Dengue virus (DENV) infection can manifest as dengue fever (DF) or dengue hemorrhagic fever (DHF), although DHF often becomes clinically apparent around defervescence. How complement components and other immune responses evolve over the course of illness from the febrile to recovery phase remains incompletely defined. This study characterized circulating complement activation and immune mediators in DF and DHF using paired febrile and early-recovery samples. Methods We conducted a multicenter prospective cohort study at five hospitals in Indonesia between November 2024 and October 2025. Patients with laboratory-confirmed dengue were classified as DF or DHF. Plasma concentrations of PTX3, C5a, IL-6, IL-10, IL-8, and CXCL10 were quantified in paired febrile and early recovery phase samples. Between-group differences, within-patient changes between the two time points, and correlations among immune mediators were assessed using appropriate statistical methods. Results We included 110 confirmed dengue cases in the analysis. PTX3 and IL-10 levels were significantly higher in DHF than in DF during early recovery, whereas no mediator differed significantly between severity groups during the febrile phase. Across phases, C5a increased significantly from febrile to early recovery in DHF but not in DF, whereas PTX3 decreased significantly in DF but not in DHF. Correlations among mediators were generally weak to moderate, with a reproducible PTX3–IL-10–CXCL10 module observed across both phases. Conclusion The measured mediators did not distinguish DF from DHF during the febrile phase, but differences emerged in early recovery, with higher PTX3 and IL-10 in DHF. Across phases, C5a increased significantly from febrile to early recovery in DHF, whereas PTX3 decreased significantly only in DF. A PTX3–IL-10–CXCL10 module was observed at both time points. Together, these patterns suggest that within-patient changes around defervescence or in the early recovery may be informative and warrant evaluation in larger, prospectively timed cohorts.